Dietary and Supplemental Vitamin C and D on Symptom Severity and Physical Function in Knee Osteoarthritis. Issue 2 (3rd July 2017) - Hung, Man; Bounsanga, Jerry; Voss, Maren W.; Gu, Yushan; Crum, Anthony B.; Tang, Philip
ABSTRACT: Vitamins C and D have been associated with decreasing pain and increasing function but these associations are not definitive. This cross-sectional study explores what relationships supplemental and dietary intake of vitamins C and D have on pain severity and physical function in patients with knee osteoarthritis. Using data from the Osteoarthritis Initiative, we performed regression analyses to examine relationships between vitamins C and D, pain, and function. Dietary vitamin D and dietary vitamin C were divided into >90th, 50th–90th, and <50th percentile. The high percentile group for supplemental vitamin D was divided into >85th percentile, whereas the high percentile group for supplemental vitamin C was divided into >90th percentile. We found the 90th/85th percentile levels of dietary and supplemental vitamin D to be positively associated with pain ( β = 0.180; p = 0.028) and inversely related to physical function ( β = −0.150, p = 0.028), respectively. Daily intake of vitamin C showed no statistical significance. We found that supplementary vitamin D was strongly associated with lessened disability for knee OA patients. The unexpected finding that associated dietary vitamin D with greater knee pain merits further study.